You can use a compass - Trumbauer, Lisa 1963 (New York Children's Pres, 2003)
Simple text and photographs describe and illustrate how to use a compass to find one's way on land, at sea, or in the air
Hurg
5
Keywords: Compass -- Juvenile literature; Compass